The causes, treatment, and outcome of pulmonary hypertension in Africa: Insights from the Pan African Pulmonary Hypertension Cohort (PAPUCO) Registry. (15th October 2016) - Thienemann, Friedrich; Dzudie, Anastase; Mocumbi, Ana O.; Blauwet, Lori; Sani, Mahmoud U.; Karaye, Kamilu M.; Ogah, Okechukwu S.; Mbanze, Irina; Mbakwem, Amam; Udo, Patience; Tibazarwa, Kemi; Damasceno, Albertino; et al.
Abstract: Background: Epidemiology, aetiology, management and outcome data for various forms of pulmonary hypertension (PH) in Africa are scarce. Methods: A prospective, multinational cohort registry of 220 consecutive patients (97% of African descent) from 9 specialist centres in 4 African countries. The antecedents, characteristics and management of newly diagnosed PH plus 6-month survival were studied. Results: There were 209 adults (median age 48 years [IQR 35, 64]) and 11 children (age range 1 to 17 years). Most adults had advanced disease - 66% WHO Functional Class III-IV, median 6-minute walk test distance of 252 m (IQR 120, 350) and median right ventricular systolic pressure 58 mm Hg (IQR 49, 74). Adults comprised 16% pulmonary arterial hypertension, 69% PH due to left heart disease, 11% PH due to lung disease and/or hypoxia, 2% chronic thromboembolic pulmonary hypertension, and 2% PH with unclear multifactorial mechanism. At 6-months, 21% of adults with follow-up data had died. On an adjusted basis (independent of sub-groups) mortality was associated with increasing functional impairment ( p  = 0.021 overall - WHO Class IV versus I, OR 1.68 [95% CI 0.13, 4.36]) and presence of combined right atrial and ventricular hypertrophy (46% - OR 2.88, 95% CI 1.45, 5.72). Children commonly presented with dyspnoea, fatigue, cough, and palpitations with six and three children, respectively diagnosed with concurrent PH associated congenital heart disease and left heart disease. Conclusions: These data provide new insights into PH from an African perspective, with clear opportunities to improve its prevention, treatment and outcomes. Trial Registration: ClinicalTrials.gov (NCT02265887).